1981
DOI: 10.2464/jilm.31.793
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Photo 1 A dendritical structure in Al-3.4% Zr alloy solidified in iron mold. (TEM)Photo 3 Small angular structure with a characteristic fringe in Al-2.4%Zr alloy solidified by the hammer quenching method. (TEM) Vol. 31, No. 12 795

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…pct Ti alloys aged between 400°C and 550°C. They also noted that the decomposition kinetics of Al 3 Ti were sluggish compared with those of Al alloyed with other elements of the same subgroup, Zr or [19] (b) Kerr et al, [36] (c) Hori et al, [75,76] and (d) Hori et al [24] Hf. Pandey and Suryanarayana [78] also compared the decomposition behavior of rapidly solidified Al alloyed with Ti, Zr, or Hf (Group 4 elements) and noted that a metastable Al 3 M (L1 2 ) ordered phase is observed in Al-Zr and Al-Hf alloys but not in Al-Ti alloys.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…pct Ti alloys aged between 400°C and 550°C. They also noted that the decomposition kinetics of Al 3 Ti were sluggish compared with those of Al alloyed with other elements of the same subgroup, Zr or [19] (b) Kerr et al, [36] (c) Hori et al, [75,76] and (d) Hori et al [24] Hf. Pandey and Suryanarayana [78] also compared the decomposition behavior of rapidly solidified Al alloyed with Ti, Zr, or Hf (Group 4 elements) and noted that a metastable Al 3 M (L1 2 ) ordered phase is observed in Al-Zr and Al-Hf alloys but not in Al-Ti alloys.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…As demonstrated in Figure 1, the marked grain refinement observed with increasing Ti concentration is due to primary precipitation of Al 3 Ti in the melt, and increasing the Ti concentration does not increase the amount of Ti retained in a-Al solid solution. The inter-relationships among solidification rates, solute concentrations, and solidified microstructures of the Al-Ti and Al-Zr binary systems have been the subject of prior studies, [19,24,36,75,76] which are summarized in Figure 8. These curves show the measured solidification rate, as a function of solute concentration, necessary to suppress primary precipitation of Al 3 Ti or Al 3 Zr, thereby obtaining supersaturated a-Al solid solution.…”
Section: Limitations On Increasing the Solute Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hori et al 19,20) have reported the relationship between the cooling rate and the solute content for AlZr alloys, which is shown in Fig. 2, and have identified processing conditions resulting in non-equilibrium solidification structure, i.e., supersaturated solid solution or L1 2 Al 3 Zr within Al.…”
Section: )mentioning
confidence: 99%
“…When melted alloys are rapidly solidi ed to form a ribbon shape at cooling rates of about 10 5 and 10 6 K/s by a single roller technique, the solid solubility increases and a nano structure is formed. For example, the microstructure of aluminum containing titanium solidi ed using a single roller was examined [5][6][7] . Furthermore, new high speci c strength aluminum alloys for use in lighter, more functional automobile components have been developed by optimization of the chemical composition and the rapid solidi cation technique [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%